Dampak Sistem Zonasi Terhadap Penerimaan Peserta Didik Baru - Faizal Chan; Agung Rimba Kurniawan; Nandatulloh Sulaiman; Rita Setiawati; Nur Fitriana; Dawiyah Dawiyah; Cindy Nurlayly (STKIP Andi Matappa Pangkep, 2019)
This study aims to describe the impact of the zoning system on student acceptance in the State Elementary School 112/I Muara Bulian, using a qualitative approach. This type of research used by researchers in this research is a descriptive case study. The population in this study is the principal, teachers, and parents of students. The data collection techniques of this study are observation, direct interviews, and documentation. Data analyze uses is the Miles and Huberman model which consists of activities namely data reduction, data presentation, and data verification. The results of this study are as follows; (1) can eliminate the frills on regarding superior and non-superior schools, (2) students can easily enroll to the school, (3) guardians of students no longer need to deliver their children because of the distance of the house and school is near, and (4) it’s difficult for guardians of students to enroll their children in school through online channels.